Evolution of the ecuadorian industrial sector and its reputation under the merco index - Buele Nugra, Irene; Aucapiña, Michelle; Solano, Santiago (Open Science Journal, 2024)
Corporate reputation is a representation of a company's performance, management, and behavior to improve results and long-term soundness. This article analyzes the evolution of the financial performance of the Ecuadorian industrial sector through financial indicators and its corporate reputation and compares it with the ranking prepared by the Corporate Reputation Business Monitor (Merco). The methodology applied focuses on the analysis of Ecuadorian industrial companies rated as the most representative according to Merco, whose financial information is obtained from the financial statements provided by the Superintendence of Companies of Ecuador. The results show that the indicators with the highest correlation are those of liquidity, with the Acid Test ratio being the most directly related to Merco at 34%, followed by the Current Liquidity indicator at 24.82%. The indicators that show a less positive correlation with Merco are the ratios of Operating Return on Equity with 3.56% and Financial Profitability with 2.26%. In conclusion, there is a direct positive relationship between the Merco index and the financial indicators of Ecuadorian industrial companies.